PENGEMBANGAN MULTIMEDIA GAME PEMBELAJARAN MATEMATIKA SMP - Heru Heru (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2018)
This has made ​​a great contribution that the use of ICT in education. Utilization of ICT which is directly in contact with the medium of education is the development of computer-assisted learning (Computer Assisted Instruction). This research is the development of multimedia instructional games of mathematics research in class VII Secondary School I Muhammadiyah Palembang. The purpose of this research is to; 1) produce an instructional multimedia math’s games class VII of the valid Secondary School; 2) produce multimedia instructional math games class VII Secondary School practically; 3) produce multimedia instructional math games class VII Secondary School which has a potential effect. The development model used in this research is a Plomp model consisting of three phase: a) preliminary research phase; b) prototype phase; c) assessment phase. Based on the data obtained  by the researcher concluded that the third prototype is being developed has a good level of practicality with the average value of the results of the analysis of student questionnaire was 83.33 (both categories) and the average value of the results of the analysis of observations is 85 (category well). Meanwhile, in terms of potential effects posed by interactive multimedia categorized very well with the results of the analysis of the average value of 92.29 and the student is otherwise completed for all the test results, the scores of all the students are more than a minimum completeness criteria (KKM’s score which is more than 60)